Proanthocyanidins in health and disease. (13th January 2016) - Bladé, Cinta; Aragonès, Gerard; Arola‐Arnal, Anna; Muguerza, Begoña; Bravo, Francisca Isabel; Salvadó, M. Josepa; Arola, Lluis; Suárez, Manuel
Abstract: Proanthocyanidins (PAs) are the most abundant flavonoids in the human diet. Several epidemiological studies connect PA consumption and health benefits and the designation of PAs as healthy compounds started at the early stages of the 20th century. The beneficial health properties of PAs are attributed to their conjugated and colonic metabolites. Therefore, gut microbial compositions can determine the effectiveness of PAs. Reciprocally, dietary polyphenols can act as prebiotics. Recently, it has also been described that PAs modulate the circadian rhythm. Biochemical and epigenetic mechanisms, including the modulation of microRNAs, allow PAs to modulate cell functionality. PA effects in metabolic diseases are also reviewed. © 2016 BioFactors, 42(1):5–12, 2016